Podoconiosis in Rwanda: Knowledge, attitudes and practices among health professionals and environmental officers. - Ursin Bayisenge; Janna Schurer; Rex Wong; Hellen Amuguni; Gail Davey (Public Library of Science (PLoS), 2020)
Background Podoconiosis is a neglected tropical disease commonly found in volcanic regions, where soil is rich in silica. It usually manifests as bilateral lower limb edema. The majority of people affected by podoconiosis are farmers who do not wear shoes. The condition was recently documented in all 30 districts in Rwanda but knowledge, attitudes and practices (KAP) of Rwandan health professionals and environmental officers towards podoconiosis are unknown. Methodology/findings The objective of this study was to assess the knowledge, attitudes and practices (KAP) of Rwandan health providers and environmental officers towards podoconiosis in order to improve patient healthcare experiences and health outcomes, and to reduce stigma against affected individuals. To achieve this goal, we administered a KAP assessment to physicians (N = 13), nurses/midwives (N = 59), community health workers (N = 226), and environmental officers (N = 38) in the third highest podoconiosis prevalence district in Rwanda (Musanze). All 336 respondents had heard of podoconiosis, but 147 (44%) respondents correctly identified soil as the only direct cause of podoconiosis. The awareness of signs and symptoms and risk groups was lower than any other category (31.5% and 47.5%, respectively). The overall attitude toward podoconiosis was positive (86.1%), with CHWs least likely to harbor negative beliefs against podoconiosis patients. One particular area where most respondents (76%) expressed negative attitude was that they saw people with podoconiosis as a threat to their own health and their family's health. Prescription of antibiotics and use of ointments/soap to manage wounds was low (5% and 32.2%, respectively), in part due to supply shortages at health facilities. Conclusions This study identified clear gaps in health provider knowledge and practices that affect patient care for those with podoconiosis. Improved access to essential medicines at health facilities and podoconiosis-focused training sessions for practicing health providers are necessary to minimize the burden and stigma of affected individuals.